MODEL DISCOVERY LEARNING BERBANTUAN QUESTIONING UNTUK MENINGKATKAN HASIL BELAJAR SUHU DAN KALOR DI SMP - Rizka Sari, Dwi Jumiah; Maria S, Haratua Tiur; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract   This study aims to improve the learning outcomes of SMP Negeri 3 Ambawang about temperature and heat by applying the discovery learning model assisted with questioning. The form of this research is pre-experimental design with the design of one group pretest-posttest. This study involved the whole class of VII D as an experimental  class, with a total of 29 students whom selected using a purposive sampling technique. The research instrument was 20 questions in the form of multiple choice learning outcomes test. Based on the results of the Wilcoxon test using SPSS 23, the Asym score of 0.000 (<0.05) was obtained so that Ha was accepted, which means that there were significant differences in student learning outcomes before and after the discovery learning model assisted with questioning. There is an increase in learning outcomes seen from the average pretest-posttest score of 34.14. The application of discovery learning model assisted with questioning is effective for improving student learning outcomes in temperature and heat material with a value of 2.88s (classified as high). The results of the study are expected to be an alternative in an effort to improve learning outcomes of students in the subject about temperature and heat.      Keywords: application, discovery learning, questioning, learning ouycomes,                     temperature and heat